Extraskeletal myxoid chondrosarcoma of thigh: a rare case report - Shah, Pinal C.; Hathilal, R. N.; Sheth, Sheetal; Gavit, Smita S. (International Journal of Research in Medical Sciences, 2021)
Extraskeletal myxoid chondrosarcoma (EMC) are a rare entity of soft tissue tumors that occur predominantly in soft tissue of lower extremities. Here we present a case of 45-year-old female presented with left thigh swelling. MRI finding suggested primary neoplastic lesion. Fine needle aspiration cytology (FNAC) suggested myxoid soft tissue neoplasm/sarcoma. Morphological examination revealed typical extraskeletal myxoid chondrosarcoma with strong immunoreactivity for vimentin and focal immunoreactivity for epithelial membrane antigen (EMA).